2022
DOI: 10.1109/tvcg.2022.3150475
|View full text |Cite
|
Sign up to set email alerts
|

Remote research on locomotion interfaces for virtual reality: Replication of a lab-based study on teleporting interfaces

Abstract: Fig. 1. The diagram on the left depicts the triangle completion task. The participant traveled sequentially to three locations marked by vertical posts (green, then yellow, then red) before attempting to point to the remembered location of the green post. Screenshots show perspective views of the three posts marking the triangle as well as the response. The top row shows the partially concordant teleporting interface, where the participant teleports to translate but rotates using the body. The top row also dep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
2
1
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
(68 reference statements)
1
4
0
Order By: Relevance
“…This experiment evaluated the effects of practice and feedback on triangle completion performance when using two teleporting interfaces: partially concordant teleporting and discordant teleporting. Task errors were higher when using the discordant teleporting interface, which lacked body rotations, and this finding is consistent with the hypothesis and with past research [7,18,19]. Practice alone led to a marginal improvement in task error for both interfaces.…”
Section: Summary Of Main Findings and Relationship To Prior Researchsupporting
confidence: 91%
See 1 more Smart Citation
“…This experiment evaluated the effects of practice and feedback on triangle completion performance when using two teleporting interfaces: partially concordant teleporting and discordant teleporting. Task errors were higher when using the discordant teleporting interface, which lacked body rotations, and this finding is consistent with the hypothesis and with past research [7,18,19]. Practice alone led to a marginal improvement in task error for both interfaces.…”
Section: Summary Of Main Findings and Relationship To Prior Researchsupporting
confidence: 91%
“…It is therefore possible that VR novices, who lack experience with VR and with teleporting interfaces, would benefit even more from practice and feedback than the experienced VR users tested in the current study. On the other hand, a study measuring triangle completion performance when teleporting found that HMD owners perform with similar accuracy to VR novices [19], perhaps because the typical usage of the teleporting interface is for tasks that require less precise spatial updating than does the triangle completion task, so this remains a question for future empirical study.…”
Section: Summary Of Main Findings and Relationship To Prior Researchmentioning
confidence: 99%
“…), VR research in spatial navigation could benefit from efforts to establish collaborations that support increased open access to virtual environment software infrastructure as well as high quality VR models of different types of spaces. Related to this, labs have found ways to expand immersive VR studies remotely by recruiting participants who have consumer-level HMDs in their homes (Kelly, Hoover, et al, 2022). This work generally replicated navigation performance found in the lab, although there were some differences that may be attributed to the expertise of the remote participants.…”
Section: Discussionmentioning
confidence: 72%
“…As a reminder, teleporting involves discrete jumps in location that exclude body-based and self-motion cues (D. Bowman et al, 1997;Bozgeyikli et al, 2016). Compared to walking, performance on a triangle completion task was worse when teleporting to translate and using the body to rotate (Barhorst-Cates et al, 2020;Barhorst-Cates, Stoker, et al, 2021;Cherep et al, 2022;Cherep et al, 2020), and worse still when teleporting to translate and rotate Kelly, Hoover, et al, 2022;Kelly et al, 2020). Yet, performance when using a joystick interface with continuous visual self-motion was no worse than walking (Barhorst-Cates et al, 2020;Barhorst-Cates, Stoker, et al, 2021), suggesting that visual cues can be sufficient for task performance (also see Riecke et al, 2002, but contrast with the findings of Klatzky et al, 1998 andLessels, 2006).…”
Section: Self-motion Cuesmentioning
confidence: 99%
“…It is therefore possible that VR novices, who lack experience with VR and with teleporting interfaces, would benefit even more from practice and feedback than the experienced VR users tested in the current study. On the other hand, a study measuring triangle completion performance when teleporting found that HMD owners perform with similar accuracy to VR novices [12], perhaps because the typical usage of the teleporting interface is for tasks that require less precise spatial updating than does the triangle completion task, so this remains a question for future empirical study.…”
Section: Discussionmentioning
confidence: 99%